Plasma proteomic platform comparison - VTE case study - Johansson, Emil (SciLifeLab Serve, 2026)
Comparing the log2FC between two plasma proteomic platforms: 1) Olink Explore HT and 2) SomaScan 11k. Case scenario of comparing VTE with I) Healthy individuals, II) other cardiovascular diseases, and III) all other diseases.
Keywords: Proteomics